Perancangan Dashboard Sistem Informasi Tindak Kriminal Pada Polres Musi Rawas Berbasis Web - Syafri Aprudi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Musi Rawas Police Resort is a government agency that provides services to the community in the form of receiving reports or complaints and handling, providing assistance and assistance including securing community activities, especially in the criminal investigation section which has activities to process criminal data. The report cannot directly show a comparison of the types of crime in one area with another. So it is necessary to make a crime rate calculation tool that can also display the calculation results in the form of a dashboard so that it can display a comparison between the crime rates of one area and another. In this study it can be concluded that a system dashboard has been created using the EIS Lifecycle method and blackbox testing which produces 5 views that are suitable for users based on valid test results.